From Western to Islāmic Social Sciences: al-Fārūqī’s View - Oudihat, Mohamed; Mumtaz Ali, Muhammad (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2026)
Abstract The globalization of modern social sciences, rooted in Western paradigms, has raised questions about their relevance, universality, and ethical foundations. The Muslim world has adopted these sciences uncritically, leading to a disconnect between their methodologies and Islamic ethical and epistemological frameworks. Ismā’īl Rājī al-Fārūqī proposed a transformative alternative: to rethink Western social sciences – their division into disciplines, their fundamental principles, methodologies, objectives, problems, and impact on the world – from a universal Islamic perspective on the world and knowledge. He proposed “Islamic social sciences” or “Ummatic sciences,” based on the Tawḥīdī paradigm. This study examines al-Fārūqī’s conceptualization of these sciences, their epistemological foundations, and their potential to address the limitations of Western paradigms. Through a qualitative textual and thematic analysis of his main writings, this study highlights the distinctive characteristics of the “Ummatic sciences,” including their ethical orientation, universal applicability, and integration of revelation and reason. The conclusions emphasize the need for a paradigm shift in the social sciences in order to align them with Islamic principles and serve the common good of humanity.